Enhancing Financial Literacy Through Educational Game-Based Learning Materials - Oktaviani, Dwi Indah; Gusnardi, Gusnardi; Caska, Caska; Suarman, Suarman; Indrawati, Henny (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to develop educational materials based on financial literacy through educational games to enhance high school students' understanding of financial literacy. Using the Research and Development (R&D) method with the 4-D model by Thiagarajan, Semmel, and Semmel, this research involves the stages of define, design, develop, and disseminate. The study was conducted at SMAN 9 Pekanbaru with subjects being tenth-grade students. Data were collected through interviews, questionnaires, and tests, and analyzed using descriptive techniques, t-tests, and N-Gain to measure the effectiveness of the instructional materials. Validation results indicated that the instructional materials had an overall average of 94.44%, categorized as highly valid. Field trials showed the practicality of the instructional materials with average responses from teachers at 95.56%, from students at 88.22%, and from observations at 88,63%. N-Gain test results showed that students' understanding increased with an average N-Gain score of 0.6594, which falls into the